A preliminary study on biological aspects of the orange-spotted grouper (Epinephelus coioides) harvested in the northern coast of Aceh, Indonesia. Issue 1 (February 2021) - Fadli, N; Damora, A; Muchlisin, Z A; Dewiyanti, I; Ramadhaniaty, M; Zhelfi, Z; Roka, N F; Fitriani, F; Rusdi, M; Nur, F M; Batubara, A S; Siti-Azizah, M N
Abstract: Considered as the least concern (LC) based on the IUCN category, the biological information of Epinephelus coioides is limited. The present study's objective was to study some biological aspects of the orange-spotted grouper harvested in the northern coast of Aceh. The fishes were collected from June - August 2020 in several fish landing sites (TPI) and fish market located in Banda Aceh and Aceh Besar district. In total, 30 fish specimens were collected in this study. The total length (TL) of the fishes ranged from 194.1-237.6 mm. Also, the weight of the fishes ranged from 100.7-176.7 g. All the collected fishes were female with the gonad maturity levels in level one (1), with the average gonad weight of 0.01 g. This study provides a reference point of some biological aspects of the orange-spotted grouper that will help develop a practical fisheries management of the species.